2019
DOI: 10.26717/bjstr.2019.16.002916
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation Role of PBK in Cell Cycle and Apoptosis of Prostate Cancer

Abstract: Objective: To investigate the effect of PBK on cell cycle and apoptosis of prostate cancer cell lines.Methods: Obtain the differences expression gene, PBK, which related to prostate cancer from high-throughput microarray, Furthermore, the cell cycle and apoptosis of prostate cancer cells were detected by flow cytometry after transfection with PBK inhibitor and overexpression plasmid.Results: After DU145/LNCaP transfection, the PBK expression levels were measured at 48 hours by RT-qPCR, compared to the blank co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…At the N-terminus of PBK protein there is an important phosphorylation site Thr-9 in which cdk1/cyclin B enables to activate. Moreover,the mitotic phosphorylation of Thr-9 is also involved in cytokinesis (Fang 2019). Domain analysis revealed that the Pkinase domain of PBK likely interacted with many other domains in the cell-cycle signaling pathway (Supplementary table).…”
Section: Functional Interaction Of Pbk With Multiple Proteins In the ...mentioning
confidence: 99%
“…At the N-terminus of PBK protein there is an important phosphorylation site Thr-9 in which cdk1/cyclin B enables to activate. Moreover,the mitotic phosphorylation of Thr-9 is also involved in cytokinesis (Fang 2019). Domain analysis revealed that the Pkinase domain of PBK likely interacted with many other domains in the cell-cycle signaling pathway (Supplementary table).…”
Section: Functional Interaction Of Pbk With Multiple Proteins In the ...mentioning
confidence: 99%